Family Harmony and the Question of National Resilience: A Maqāṣid al-Sharī‘ah Perspective - Arif Sugitanata; Ahmet Arıtürk; Ahmad Rajafi; Fayaz Mahmadah; Wardatun Nadhiroh (Indonesian Journal of Islamic Law, 2026)
Indonesia’s national resilience is currently facing multidimensional pressures that have a direct impact on social stability, including family harmony as the smallest yet strategically significant social unit. Departing from this reality, this study aims to explain the urgency of national resilience in shaping and maintaining family harmony, while also exploring its contribution through the perspective of maqāṣid al-sharīʿah. Employing a qualitative approach based on a literature review, this research examines a wide range of academic sources, including books, scholarly journal articles, findings from authoritative research institutions, and Islamic normative frameworks, to construct an in-depth theoretical synthesis. The findings indicate that various dimensions of national resilience, such as economic, ideological, cultural, security, digital resilience, equitable development, and institutional integrity, can be understood as structural conditions that shape the quality and stability of relationships within the family. Accordingly, family harmony in this article is positioned not as a determinative empirical indicator, but as an analytical and conceptual indicator for assessing the effectiveness of the national resilience system. When the state fails to fulfil one or more of these aspects, families are exposed to structural pressures that threaten communication, caregiving roles, role modelling, and emotional stability. From the perspective of maqāṣid al-sharīʿah, national resilience is shown to support efforts to protect the five fundamental principles, namely religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Therefore, family harmony is not merely an expression of interpersonal relations but also an indicator of the effectiveness of the national resilience system. In this context, the study offers conceptual novelty by positioning family harmony not solely as the outcome of internal household dynamics, but as a socio-legal indicator of the quality of national resilience. This approach extends the study of maqāṣid al-sharīʿah from the normative domain of family law into a structural analysis that links state responsibility with the lived realities of family life. Thus, this article not only synthesises existing ideas but also constructs a new analytical framework that is relevant to the study of Islamic law and social governance.